Digital Media and Technology in Arabic Language Learning - Faiqoh, Putri Kholida; Gadoum, Hamida; Baity, Anggi Nurul; Azza, Fahema Hadia (Journal of Arabic Language Teaching, 2025)
Media and technology have brought significant transformations in Arabic language learning, creating new opportunities to improve the quality, accessibility and effectiveness of learning. This study uses a library research method to explore media and technology in Arabic language learning. Data were collected from various relevant written sources, including books, scientific journals, and online articles that discuss media and technology in language education. Various findings show that the integration of technologies, such as e-learning platforms, mobile applications, gamification, as well as Virtual Reality (VR) and Augmented Reality (AR), has successfully increased students' motivation, engagement, and Arabic language competence. Digital media not only makes learning more engaging and interactive, but also allows personalization of learning according to individual needs and learning pace. Some key recommendations include teacher training in the use of technology, development of quality digital content, and collaboration between the government, educational institutions and the private sector.